Association between peripheral blood cells mitochondrial DNA content and severity of coronary heart disease. (June 2017) - Liu, Li-Peng; Cheng, Kang; Ning, Ming-An; Li, Hong-Hong; Wang, Hai-Chang; Li, Fei; Chen, Shu-Ying; Qu, Fa-Lin; Guo, Wen-Yi
Abstract: Background and aims: Leukocyte mitochondrial DNA (mtDNA) content reflects the oxidant-induced cell damage, which has been observed in a wide range of cardiovascular diseases. However, whether it correlates with coronary heart disease (CHD), which closely relates to oxidative stress, has never been elucidated before. The aim of this study was to explore association between mtDNA content and the presence and severity of CHD. Methods: The study population consisted of 400 individuals (290 with CHD and 110 controls). A quantitative real-time PCR was performed to measure the relative content of mtDNA in peripheral blood cells (PBCs). Gensini score was used to evaluate the severity of coronary stenotic lesions. An unconditional multivariate logistic regression was developed to estimate the association between CHD risk and mtDNA content by using odds ratio (OR). This study is registered with ClinicalTrials.gov, numberNCT02500823 . Results: CHD patients, compared to controls, had lower mtDNA content (median, 0.78 vs. 0.83, p  < 0.001), and mtDNA levels significantly decreased following an increasing Gensini score ( p  < 0.001). By using the first (highest mtDNA content) quartile of mtDNA content of controls as reference, the adjusted ORs (95% CIs) for individuals in the second, third and highest quartile of mtDNA content were 1.78 (95% CI, 1.15–3.51), 2.21 (95% CI, 1.65–3.74) and 4.83 (95% CI, 2.67–8.64), respectively ( p for trend <0.001). Conclusions: These preliminary results suggest that expression of mtDNA may be associated with atherogenesis. The level of peripheral blood mtDNA in predicting the severity of coronary atherosclerosis may have a relatively certain value. Highlights: Coronary heart disease (CHD) patients, compared to controls, had significantly lower mtDNA content. Lowest quartile mtDNA content conferred a more than four-fold increased risk of CHD compared with highest quartile. mtDNA content may serve as a novel biomarker in predicting CHD development and quantifying severity of CHD.